Stolleagrion foghnielseni (Odonata, Cephalozygoptera, Dysagrionidae) gen. et sp. nov.: a new odonatan from the PETM recovery phase of the earliest Ypresian Fur Formation, Denmark - Simonsen, Thomas J.; Archibald, S. Bruce; Rasmussen, Jan A.; Sylvestersen, René L.; Olsen, Kent; Ware, Jessica L. (Zootaxa, 2024)
We describe the new genus and species Stolleagrion foghnielseni n. gen. et sp. from the Fur Formation in northwestern Denmark based on a single fossil wing. This is the first odonatan described from the earliest part of the PETM recovery phase of the early Eocene. A combination of nine wing character states are considered to be diagnostic of the Dysagrionidae Cockrell only together with the cephalozygopteran head; however, the combination of these nine plus the presence of Ax0 is also diagnostic without the head. By this, we assign Stolleagrion foghnielseni to the Dysagrionidae and reassess the position of other odonates previously treated as cf. Dysagrionidae.